Three-phase open-end load supplied by a dual AC-AC converter based on optimum-amplitude Venturini method - Beladel, Abdelkader; Kouzou, Abdellah; Hafaifa, Ahmed; Mahi, Djilali; Sünter, Sedat (ICPE Electra Publishing House, 2018)
This paper deals with the study of a dual three to three matrix converters feeding an open-end three-phase load. Where the both matrix converters constituting the dual topology are controlled using the Optimum-Amplitude Venturini modulation techniques. Indeed, the main objective of using such modulation technique with the presented load topology is to achieve the requirement of improving the performance of the input power quality and the quality of the output voltage of the used dual matrix converter. In the same time, to ensure the control of the three phases of the load independently and to avoid the appearance of the common mode voltage, which appears usually in the conventional star load connection. Based on the obtained simulation results of the output voltages quality, the input currents waveforms and the resulting common mode voltage, it can be said that the effectiveness of the proposed control with the used load topology is confirmed and validated clearly. Furthermore, the presented topology and its modulation control are presenting a promising solution in several applications, especially for electrical machines in industrial processes and chains to improve their operating performances. © 2018, ICPE Electra Publishing House. All rights reserved.
Keywords: Dual matrix converter; Matrix converter; Modulation technique; Open-end load; Venturini algorithm